PLAG (1-Palmitoyl-2-Linoleoyl-3-Acetyl-rac-Glycerol) Modulates Eosinophil Chemotaxis by Regulating CCL26 Expression from Epithelial Cells - Jeong, Jinseon (PLoS One, 2016)
Increased number of eosinophils in the circulation and sputum is associated with the severity of asthma. The respiratory epithelium produces chemokine (C-C motif) ligands (CCL) which recruits and activates eosinophils. A chemically synthesized monoacetyl-diglyceride, PLAG (1-palmitoyl-2-linoleoyl-3-acetyl-rac-glycerol) is a major constituent in the antlers of Sika deer (Cervus nippon Temminck) which has been used in oriental medicine. This study was aimed to investigate the molecular mechanism of PLAG effect on the alleviation of asthma phenotypes. A549, a human alveolar basal epithelial cell, and HaCaT, a human keratinocyte, were activated by the treatment of interleukin-4 (IL-4), and the expression of chemokines, known to be effective on the induction of eosinophil migration was analyzed by RT-PCR. The expression of IL-4 induced genes was modulated by the co-treatment of PLAG. Especially, CCL26 expression from the stimulated epithelial cells was significantly blocked by PLAG, which was confirmed by ELISA. The transcriptional activity of signal transducer and activator of transcription 6 (STAT6), activated by IL-4 mediated phosphorylation and nuclear translocation, was down-regulated by PLAG in a concentration-dependent manner. In ovalbumin-induced mouse model, the infiltration of immune cells into the respiratory tract was decreased by PLAG administration. Cytological analysis of the isolated bronchoalveolar lavage fluid (BALF) cells proved the infiltration of eosinophils was significantly reduced by PLAG. In addition, PLAG inhibited the migration of murine bone marrow-derived eosinophils, and human eosinophil cell line, EoL-1, which was induced by the addition of A549 culture medium.